Analisis Data Penelitian Pendidikan: Konsep, Prosedur, dan Implementasi pada Pendekatan Kualitatif dan Kuantitatif - Adang Ridwan; Agus Salim; Ria Karmila; Mahdayeni Mahdayeni; Harlina Harja; Rian Septiawan (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2026)
Data analysis is a fundamental stage in educational research because it determines the validity, credibility, and quality of research findings. The different philosophical paradigms underlying qualitative and quantitative approaches require distinct concepts, procedures, and analytical techniques. This study aims to examine the concepts, procedures, and implementation of data analysis in educational research using both qualitative and quantitative approaches. A literature review method was employed by analyzing books, scientific journal articles, and other relevant academic references related to educational research methodology. The findings indicate that qualitative data analysis emphasizes an interactive and iterative process involving data reduction, data display, conclusion drawing, and verification to produce credible and meaningful interpretations. In contrast, quantitative data analysis relies on systematic statistical procedures, including descriptive and inferential analyses, to test hypotheses, identify relationships among variables, and support objective decision-making. Although both approaches differ in their analytical orientation and techniques, they share the need for systematic, objective, valid, and rigorous procedures to ensure the accuracy and trustworthiness of research findings. Understanding these differences enables researchers to select analytical methods that are appropriate to their research objectives, designs, and data characteristics. This study contributes to a broader understanding of educational research methodology and provides practical guidance for researchers, educators, and university students in implementing effective and appropriate data analysis techniques.